Postharvest quality of ‘Roxo de Valinhos’ fig fruits grown in semi-arid conditions - Oliveira Silva, Francisco Sidene; Castro Pereira, Eduardo; Mendonça, Vander; de Medeiros Câmara, Francisco Mickael; Alves Pereira, Gustavo; Cabral dos Santos, Elizangela (Comunicata Scientiae, 2017)
Aiming to evaluate the postharvest quality of ‘Roxo de Valinhos’ fig fruits grown in semi-arid conditions, this experiment was carried out in November, 2014, where fig fruit variety ‘Roxo de Valinhos’ were harvested from plants located at the didactic orchard of the Federal Rural University of Semi-Arid (UFERSA), Mossoró-RN, Brazil. Fruits were randomly harvested from 30 fig plants, spaced 2 m x 1.5 m, with 2 years old, according to three the fruit development stages (50%, 75% and 100% mature). The fruits were analyzed in Postharvest Physiology Laboratory, where the physical and chemical characteristics were evaluated, using 10 fruits for each stage. The evaluated characteristics were: weight, length, diameter, firmness, soluble solids, pH, titratable acidity and vitamin C. For the physical characteristics, fruits 100% mature presented the best results for weight, length and diameter, except for firmness which in fruits 50% mature presented the best results. For the chemical characteristics, only the soluble solid variable was signiicant and fruits 100% mature showed the best result, in this way, the fig tree ‘Roxo de Valinhos’ achieved the postharvest fruit quality and is viable for the semiarid region of the Rio Grande Norte State.